Development of safe operation technology of crude oil pipeline in permafrost regions - Chen, Pengchao; Ma, Yunbin; Li, Rui; Cai, Yongjun; Li, Qiujuan; Li, Guoyu; Liu, Xiaoben (Journal of Pipeline Science and Engineering, 2024)
China Mohe‒Daqing Pipeline is the world first large diameter and positive temperature buried pipeline that crosses the unstable and discontinuous permafrost regions. The permafrost along the pipeline is characterized by its high temperature, large ice content, high sensitivity to external disturbance and extremely poor thermal stability. Thus, it is a great global engineering challenge to lay and operate a stable positive temperature pipeline under the harsh conditions of “permafrost land, frigid environment and fragile ecology” while, at the same time, protecting its fragile ecological environment. Herein, the characteristics of permafrost along the pipeline were systematically analyzed, and the current scientific and technical problems in the phases of pipeline designing, constructing and operating were put forward. This thesis made significant innovative breakthroughs in the coupling mechanism of permafrost and pipelines, the design and control of hydro-thermal stable environment for permafrost and pipeline, and the monitoring, prevention and control of permafrost and pipeline disasters, thus creating a complete set of key technical systems for pipeline construction and operation in frozen soil regions. Through analyzing the performance of this system in recent ten years, it is verified that the technical achievements served to the high-quality construction and stable operation of the pipeline.